IMPACT OF ADHOCRACY WORK CULTURE ON EMPLOYEE’S JOB IN COMPARISON BETWEEN PUBLIC AND PRIVATE SECTOR BANKS IN BENGALURU CITY - Shivappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The public invests in financial organizations' cultures, just like it does in everything valuable. The standards and ideals of a bank are developed through teamwork and deeds rather than talks. Some banking institutions decide to fire personnel who don't manage in accordance with the principles and conduct that other staff members uphold. The main objective of the study is to explore an impact of adhocracy work culture on employee’s job in comparison between public and private sector banks in Bengaluru city. Descriptive research methodology was followed in the present study. Researcher has collected all the primary data from the employee’s job s of these branches randomly. The researcher has designed separate questionnaires followed by interview to get complete details for the study for both bank especially the employee’s working in public and private sector banks. These questionnaires were constructed based on 5 point Likert’s scale. To collect the data related to work culture and job satisfaction, the employees of both selected public sector banks and private sector banks working in different cadres in Bangalore City were targeted. As per the convenience of the researcher, 2127 bank employees were reached to issue and fill out the questionnaire, out of which 1195 responded, and the response rate is 56%. The research demonstrates the unique contribution for the adhocracy variables such as relational work culture, facilitating work culture, able to acquire skills and ability to adapt to the changes, attitudes, values, skills, and power of a group or individual depending on job risk., learning is encouraged, acceptance of continuous change, and career opportunities. and the work environment is highly flexible and adaptive, for the changes have a positive association with employees’ job satisfaction in public sector banks. The results revealed that there is a unique contribution for the variables, such as dynamic and entrepreneurial work environments. followed by the ability to acquire skills and the ability to adapt to the changes in innovation, new ideas, and creativity. Encourages to take risks. Bank tolerates failure and re-attains for success. Learning is encouraged, as is product, process, and management innovation. and the work environment is highly flexible and adaptive for the changes significant influence on employees’ job satisfaction in private sector banks.